Estimation of differential code bias and ionospheric TEC based on the SUMT correction method - LIAO Siming; SHANG Junna; SU Mingkun (Dianxin kexue)
The modeling of the regional ionosphere was implemented based on spherical harmonic functions, and the regional differential code bias (DCB) and total electron content (TEC) were calculated. To correct anomalies in vertical total electron content (VTEC) values at grid points, a sequential unconstrained minimization technique (SUMT) correction method was proposed. Using dual-frequency observation data from six International GNSS Service (IGS) network stations, a regional ionospheric VTEC model was established, and the satellite inter-frequency DCB for one month were estimated. These estimates were compared with the products published by the ionosphere center of the Chinese Academy of Sciences (CAS), and an accuracy analysis was performed. The results show that all satellite DCB differences were within 0.42 ns, with 87.5% of the differences within 0.4 ns and 78.1% within 0.2 ns. The average deviation of the inter-frequency DCB was generally less than 0.4 ns, and the standard deviation (STD) of the estimated GPS satellite DCB sequence was less than 0.1 ns. A regional ionospheric model with a latitude and longitude range of 5°E～25°E and 40°N～60°N was established. The VTEC modeling results were compared with the GIM products released by CAS, showing that the overall time-point differences were within 4 TECU, with over 90% of regional differences within 2 TECU. The estimated results exhibit good consistency with the CAS products.